2006
DOI: 10.12968/ijpn.2006.12.1.20392
|View full text |Cite
|
Sign up to set email alerts
|

Supportive and palliative care needs identified by multiple sclerosis patients and their families

Abstract: Given the duration, range of symptoms and distress often associated with MS, the findings of this research raise the important question of the role of palliative services in supporting the person with MS and his/her family.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
77
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(80 citation statements)
references
References 14 publications
3
77
0
Order By: Relevance
“…4 6 found that caregivers agreed most with the following statements: "I receive support from my church" and "I receive help from community organizations," both interdependence needs. The findings of the present study are also consistent with those of other studies that have highlighted needs related to interdependence, such as obtaining help from other family members and friends, 43,67 receiving support from community sources, 48 and having enough money to meet their needs. 48,49 Previous researchers also found that caregivers frequently endorsed other specific needs, including the need for brief periods of relief from caregiving for rest and relaxation and to visit a doctor to reduce stress, discuss feeling "down," or manage health problems (eg, heart disease, high blood pressure, and flu/cold symptoms).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…4 6 found that caregivers agreed most with the following statements: "I receive support from my church" and "I receive help from community organizations," both interdependence needs. The findings of the present study are also consistent with those of other studies that have highlighted needs related to interdependence, such as obtaining help from other family members and friends, 43,67 receiving support from community sources, 48 and having enough money to meet their needs. 48,49 Previous researchers also found that caregivers frequently endorsed other specific needs, including the need for brief periods of relief from caregiving for rest and relaxation and to visit a doctor to reduce stress, discuss feeling "down," or manage health problems (eg, heart disease, high blood pressure, and flu/cold symptoms).…”
Section: Discussionsupporting
confidence: 91%
“…The findings of the present study are also consistent with those of other studies that have highlighted needs related to interdependence, such as obtaining help from other family members and friends, 43,67 receiving support from community sources, 48 and having enough money to meet their needs. 48,49 Previous researchers also found that caregivers frequently endorsed other specific needs, including the need for brief periods of relief from caregiving for rest and relaxation and to visit a doctor to reduce stress, discuss feeling "down," or manage health problems (eg, heart disease, high blood pressure, and flu/cold symptoms). 45,46 Other needs reported by researchers were help with accomplishing all that is expected of the caregiver, as well as general daily assistance from others.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations